2006
DOI: 10.4278/0890-1171-21.2.85
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 10,000 Steps per Day Goal in Overweight Adults

Abstract: A 10,000 steps (d(-1) exercise prescription resulted in weight loss over 36 weeks in previously sedentary, overweight/obese adults. Adherence to the step goal had a marked effect on the outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
78
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(87 citation statements)
references
References 14 publications
(17 reference statements)
5
78
0
4
Order By: Relevance
“…However, this approach runs the risk that inexpert users will set goals that are either too difficult or too easy and that do not, therefore, provide optimal motivation [33]. In contrast, in Fish'n'Steps [25] goals are set at a modest level by automatically using baseline step-counts as reference points and taking the findings of previous studies as a guide to what users could reasonably be expected to attain.…”
Section: Goal Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this approach runs the risk that inexpert users will set goals that are either too difficult or too easy and that do not, therefore, provide optimal motivation [33]. In contrast, in Fish'n'Steps [25] goals are set at a modest level by automatically using baseline step-counts as reference points and taking the findings of previous studies as a guide to what users could reasonably be expected to attain.…”
Section: Goal Settingmentioning
confidence: 99%
“…It is "readily repeatable, self-reinforcing and habit-forming" [31] and is the most widely accessible type of exercise because it is inherently safe, requires no special skills, location or equipment and can easily be included in domestic and work routines [32]. However, most residents of advanced economies take far less than the daily total of 10,000 steps generally recommended for good health [5,10,20,29,33].…”
Section: Introductionmentioning
confidence: 99%
“…Walking is one simple, convenient, and inexpensive physical activity in which adults can engage more frequently. Research attests to the health benefits (e.g., reduced blood pressure, body mass index, and waist and hip circumference; improved insulin sensitivity) of walking 10,000 steps (approximately 8 km) on most days of the week (Iwane et al, 2000;Schneider, Bassett, Thompson, Pronk, & Bielak, 2006;Yamanouchi et al, 1995). Further, the recommendation to walk 10,000 steps per day is consistent with the CDC's guidelines because individuals who walk 10,000 steps per day are likely to elevate their heart rates to a moderate-intensity range for at least 30 min (Le Masurier, Sidman, & Corbin, 2003).…”
mentioning
confidence: 99%
“…2 Pedometers, which are inexpensive movement counters that can easily and accurately measure the number of steps a person has taken, have greatly advanced the objective measurement of physical activity patterns in free-living populations. 3,4 A variety of pedometer-based intervention strategies have been used, including some that promote achievement and sustainability of 10,000 steps per day [5][6][7] and others which advocated alternative activity goals which typically involves incremental increases over baseline throughout the intervention. [8][9][10] In a recent systematic review of 18 observational pedometer studies and 8 randomized controlled trials, Bravata and colleagues concluded that pedometer users showed significant decreases in body mass index (BMI) and intervention participants exhibited significant decreases in systolic blood pressure.…”
mentioning
confidence: 99%